Writing intimacy into feminist geography - Moss, Pamela; Donovan, Courtney (Taylor & Francis, 2017)
Intimacy, expressed through the feelings and sensations of the researcher, is bound up in the work of a feminist geographer. Tapping into this intimacy and including it in academic writing facilitates a grasping of the effects of power in particular places and initiates a discussion about how to access and tease out what constitutes the intimate both ethically and politically throughout the research process. This collection provides valuable reflections about intimacy in the research process - from encounters in the field, through data analysis, to the various pieces of written work. A global and heterogeneous pool of scholars and researchers introduce personal ways of writing intimacy into feminist geography. ​ As authors expand existing conceptualizations of intimacy and include their own stories, chapters explore the methodological challenges of using intimacy in research as an approach, a topic and a site of interaction. The book is valuable reading for students and researchers of Geography, as well as anyone interested in the ethics and practicalities of feminist, critical and emotional research methodologies.
Keywords: LGBTQIA2+; approches et analyses; autobiographie; discipline; ethnographie; géographie; identités LGBTQIA2+; intimité; méthodologie; queer; sciences humaines; sociologie; thématiques; émotions; éthique

Critical geographies and the uses of sexuality: deconstructing queer space - Oswin, Natalie (Progress in Human Geography, 2008)
Scholarship on queer geographies has called attention to the active production of space as heterosexualized and has levelled powerful critiques at the implicit heterosexual bias of much geographical theorizing. As a result, critical geographers have begun to remark upon the resistance of gays, lesbians and other sexual subjects to a dominant heterosexuality. But such a liberal framework of oppression and resistance is precisely the sort of mapping that poststructuralist queer theory emerged to write against. So, rather than charting the progress of queer geographies, this article offers a critical reading of the deployment of the notion of `queer space' in geography and highlights an alternative queer approach that is inseparable from feminist, materialist, postcolonial and critical race theories.
Keywords: LGBTQIA2+; approches et analyses; architecture; cours; discipline; espace; géographie; hétéronormativité; premier cycle; queer; résistance; sciences humaines; soc2014; thématiques